2000
DOI: 10.1152/ajpendo.2000.278.4.e677
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fructose and glucose on plasma leptin, insulin, and insulin resistance in lean and VMH-lesioned obese rats

Abstract: To determine the influence of dietary fructose and glucose on circulating leptin levels in lean and obese rats, plasma leptin concentrations were measured in ventromedial hypothalamic (VMH)-lesioned obese and sham-operated lean rats fed either normal chow or fructose- or glucose-enriched diets (60% by calories) for 2 wk. Insulin resistance was evaluated by the steady-state plasma glucose method and intravenous glucose tolerance test. In lean rats, glucose-enriched diet significantly increased plasma leptin wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 35 publications
(33 reference statements)
2
33
1
1
Order By: Relevance
“…In support of this hypothesis, Yoshino et al (69) showed that in streptozotocintreated, diabetic, hypoinsulinemic rats, fructose feeding increased plasma insulin levels. More recently, Suga et al (70) reported that dietary fructose caused substantial insulin resistance and hyperinsulinemia in both ventromedial hypothalamic-lesioned obese and sham-operated lean rats. Dirlewanger et al (71) also showed that in healthy humans, fructose infusion induced hepatic and extrahepatic insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this hypothesis, Yoshino et al (69) showed that in streptozotocintreated, diabetic, hypoinsulinemic rats, fructose feeding increased plasma insulin levels. More recently, Suga et al (70) reported that dietary fructose caused substantial insulin resistance and hyperinsulinemia in both ventromedial hypothalamic-lesioned obese and sham-operated lean rats. Dirlewanger et al (71) also showed that in healthy humans, fructose infusion induced hepatic and extrahepatic insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…After 14 days of intracerebroventricular injection, animals were fasted 6-7 h before insulin sensitivity was assessed by the SSPG method. This method was originally developed by Reaven and colleagues (43,44) and modified by Suga et al (40). Briefly, rats were anesthetized with pentobarbital (50 mg/kg), and cannulas were implanted in the right jugular vein and carotid artery.…”
Section: Animalsmentioning
confidence: 99%
“…Suga et al (2000) suggested that fructose feeding decreases the efficacy of insulin extraction by the liver which retards insulin clearance from the circulation. Hepatic metabolism of fructose leads to alterations in the activities of key enzymes of glucose metabolism Southgate (1995) and activation of stress sensitive pathways that may desensitize insulin signaling Kelley et al (2003).…”
Section: Discussionmentioning
confidence: 99%